The Role of Short-Range Disorder in BaWO4 Crystals in the Intense Green Photoluminescence - Anicete-Santos, Marcos; Picon, Francini C.; Alves, Claudio N.; Pizani, Paulo S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Amer Chemical Soc, 2011)
An intense and broad visible photoluminescence (PL) band was observed at room temperature in short-range disordered BaWO4 crystals. The scheelite crystalline BaWO4 powders prepared by the polymeric precursor method and annealed at different temperatures were structurally characterized by means of X-ray diffraction and Fourier transform (FT) Raman spectroscopy measurements. Quantum-mechanical calculations indicated that the disorder at short range only of Ba atoms in the BaWO4 lattice has a very important role in the charge transfer involved in the intense green PL emission. This indication was detected and confirmed by means of FT Raman spectroscopy measurements. The experimental and theoretical results are in good agreement, both showing the specific type of structural disorder that is the most favorable condition for generating the most intense green PL emission in the scheelite BaWO4 lattice.